Ответы и объяснения

2013-04-23T14:37:23+04:00

42b+7b^2-b^2+b+20=0

6b^2+43b+20=0

D=1849-480=1369

b1=(-43-37)/12=-6.6666....

b2=(-b+37)/12=0,5

2013-04-23T14:39:59+04:00

Выражение: 7*b*(6+b)-(b-5)*(b+4)

Ответ: 43*b+6*b^2+20

Решаем по действиям:

1) 7*(6+b)=42+7*b

2) (42+7*b)*b=42*b+7*b^2

3) (b-5)*(b+4)=b^2-b-20

4) 42*b+7*b^2-(b^2-b-20)=42*b+7*b^2-b^2+b+20

5) 7*b^2-b^2=6*b^2

6) 42*b+b=43*b

Решаем по шагам:

1) (42+7*b)*b-(b-5)*(b+4)

2) 42*b+7*b^2-(b-5)*(b+4)

3) 42*b+7*b^2-(b^2-b-20)

4) 42*b+7*b^2-b^2+b+20

5) 42*b+6*b^2+b+20

6) 43*b+6*b^2+20